Preclinical characterization and clinical translation of pharmacodynamic markers for MK-5890: a human CD27 activating antibody for cancer immunotherapy. Issue 9 (13th September 2022) - Guelen, Lars; Fischmann, Thierry O; Wong, Jerelyn; Mauze, Smita; Guadagnoli, Marco; Bąbała, Nikolina; Wagenaars, Jozef; Juan, Veronica; Rosen, David; Prosise, Winnie; Habraken, Maurice; Lodewijks, Imke; et al.
Abstract : Background: Immune checkpoint inhibitors (ICI) have radically changed cancer therapy, but most patients with cancer are unresponsive or relapse after treatment. MK-5890 is a CD27 agonist antibody intended to complement ICI therapy. CD27 is a member of the tumor necrosis factor receptor superfamily that plays a critical role in promoting responses of T cells, B cells and NK cells. Methods: Anti-CD27 antibodies were generated and selected for agonist activity using NF-кB luciferase reporter assays. Antibodies were humanized and characterized for agonism using in vitro T-cell proliferation assays. The epitope recognized on CD27 by MK-5890 was established by X-ray crystallography. Anti-tumor activity was evaluated in a human CD27 knock-in mouse. Preclinical safety was tested in rhesus monkeys. Pharmacodynamic properties were examined in mouse, rhesus monkeys and a phase 1 dose escalation clinical study in patients with cancer. Results: Humanized anti-CD27 antibody MK-5890 (hIgG1) was shown to bind human CD27 on the cell surface with sub-nanomolar potency and to partially block binding to its ligand, CD70. Crystallization studies revealed that MK-5890 binds to a unique epitope in the cysteine-rich domain 1 (CRD1). MK-5890 activated CD27 expressed on 293T NF-κB luciferase reporter cells and, conditional on CD3 stimulation, in purified CD8+ T cells without the requirement of crosslinking. Functional Fc-receptor interaction was required to activate CD8+ T cells in an ex vivo tumor explant system and to induce antitumor efficacy in syngeneic murine subcutaneous tumor models. MK-5890 had monotherapy efficacy in these models and enhanced efficacy of PD-1 blockade. MK-5890 reduced in an isotype-dependent and dose-dependent manner circulating, but not tumor-infiltrating T-cell numbers in these mouse models. In rhesus monkey and human patients, reduction in circulating T cells was transient and less pronounced than in mouse. MK-5890 induced transient elevation of chemokines MCP-1, MIP-1α, and MIP-1β in the serum of mice, rhesus monkeys and patients with cancer. MK-5890 was well tolerated in rhesus monkeys and systemic exposure to MK-5890 was associated with CD27 occupancy at all doses. Conclusions: MK-5890 is a novel CD27 agonistic antibody with the potential to complement the activity of PD-1 checkpoint inhibition in cancer immunotherapy and is currently undergoing clinical evaluation.